This is not a hoax : unsettling truth in Canadian culture - Jessup, Heather (Wilfrid Laurier University Press, 2019)
"It's about hoaxes in Canadian culture. It shows how some contemporary artists and writers disrupt the curatorial and authorial practices of Canada's most respected cultural institutions (art galleries, museums, publishers) in order to foment and celebrate discomfort, imagination, empathy, and change."--